DEVELOPMENT OF AN RTM FILLING STRATEGY FOR AEROSPACE PARTS USING ANSYS FLUENT - Faisal Habib Boedhi W., Fahmi
Resin Transfer Molding (RTM) is a method to construct aerospace parts of composites. In the development stage, simulation of RTM filling process is important to minimize trial and error in the production. Simulations can be done to investigate the effect of inlet and outlet positions, injection pressure, as well as permeabilities to the filling pattern during the RTM process. In this work, filling simulations are done to investigate various filling scenarios on an aircraft door frame edge member, by varying some parameters. The inlet position and pressure are varied to find out the most effective injection pressure for the edge member. The permeability of race tracking is also varied to investigate different scenarios of filling process. Divergence that occurred during the simulations is also discussed. There are some things that may cause divergence during the simulation of the edge member. The simulations from inlet pressure variation result in some good results. However, none of them results a fully filled part, as air gaps still occurred in the end results. Variations on the permeability of rounded race tracking also do not lead to a fully filled part. Instead, permeability variation on the rounded race tracking often leads to divergence. Solution comes when the permeability of both rounded race tracking and pinch-off race tracking is varied. Using the permeability value of the rounded and pinch-off race tracking twice of the preform permeability, and injection pressure of 501325 Pa on both inlets, the simulation results in a fully filled part. The fully filled result also improved by increasing the injection pressure on Inlet-1 into 801325 Pa. Fully filled parts are resulted using the pressure setting, with the permeability values of rounded and pinch-off race tracking are twice and 10 times of the preform permeability.